Classification of Left Ventricular Diastolic Function Using American Society of Echocardiography Guidelines: Agreement among Echocardiographers. Issue 9 (1st April 2013) - Chapman, Carrie B.; Ewer, Steven M.; Kelly, Annie F.; Jacobson, Kurt M.; Leal, Miguel A.; Rahko, Peter S.
<x xml:space="preserve">Abstract</x> Guidelines for assessing diastolic function by echocardiography are continually being updated. Our ability to use available guidelines effectively has not been completely investigated. Six trained echocardiographers were asked to interpret 105 echocardiograms using current American Society of Echocardiography (ASE) algorithms for interpretation of diastolic grade and estimation of left atrial (LA) pressure. Diastolic grade was categorized as normal, mild, moderate, or severe dysfunction. The presence or absence of elevated LA pressure was determined using a second ASE algorithm. As a reference comparison for level of agreement, left ventricular ejection fraction was visually determined. By the ASE algorithm, 29 subjects (28%) met all measurement criteria in their assigned grade and 57 subjects (55%) met all or all but one criterion of their assigned grade. Of the 45 subjects (43%) for whom the guidelines disagreed by more than 1 criterion, the readers debated between normal and moderate dysfunction in 22% or mild and moderate diastolic dysfunction in 31%. Percent inter‐reader agreement and kappa values were 76% (0.7) for determining diastolic grade, 84% (0.67) for determining elevated LA pressure, and 84% (0.67) for estimation of ejection fraction, the reference standard. For all subjects, if multiple echocardiographic criteria failed to fit into the proposed guidelines, agreement fell to 66% (0.58) for determining diastolic grade and 74% (0.48) for determining LA pressure. There is reasonable agreement estimating diastolic grade and LA pressure using current guidelines. Further refinements in the definition of mild and moderate dysfunction may improve agreement.